Total Synthesis of Lamellarins D, H, and R and Ningalin B - Li, Qingjiang; Jiang, Jingqian; Fan, Aili; Cui, Yuxin; Jia, Yanxing (Organic letters, 2011)
A concise total synthesis of lamellarins D (7 steps), H (7 steps), and R (5 steps) and ningalin B (5 steps) is achieved starting from the corresponding aldehydes and amines. The synthesis features three oxidative reactions as key steps in a biomimetic manner, involving an AgOAc-mediated oxidative coupling reaction to construct the pyrrole core, a Pb(OAc)4-induced oxidative cyclization to form the lactone, and Kita’s oxidation reaction to form the pyrrole−arene C−C bond.